Characteristics of inpatients with nontuberculous mycobacterial infections in a highly complex hospital in Colombia - Franco Eduardo Montúfar; Camilo A. Madrid; María C. Montufar; Carolina Aguilar; Carolina Saldarriaga; Miguel A. Mesa; Alicia Quiroga; Carlos E. Builes; John J. Zuleta; Olga L. Molina (Asociación Colombiana de Infectología, 2014)
Background: Nontuberculous mycobacteria (NTM) infections has been described more frequently in recent years, especially in immunosuppression conditions and after cosmetic surgical procedures. The NTM include species of the genus Mycobacterium , other than Mycobacterium tuberculosis complex and Mycobacterium leprae. Objective: To describe the demographic and clinical characteristics of Colombian in-patientswith NTM infections. Methodology: A retrospective descriptive study. Results: In 187 patients with culture- confirmed mycobacterial infection, 17 (9,1%) had NTM.The mean age was 38,4 ± 19,2 and 58,82% were men. Major comorbidities were: HIV/AIDS(41,1%), diabetes mellitus (23,5%), chronic renal disease (17,6%), immunosuppressive therapy(17,6%) and neoplasms (17,6%). In patients co-infected with HIV, CD4 count was <50 in 85,7%.The most frequent species were M. avium complex (MAC) in 35,2%, M. abscessus in 17,6% and M. chelonae in 11,7%. Infections were disseminated (35,2%), pulmonary (23,5%), skin and soft tissue (17,6%) and in gastrointestinal system (11,7%). The average hospital stay was 22,1 day sand 23,5% required intensive care unit. Overall mortality was 23,5%. Conclusion: MNT infections cause a number of pathological conditions, being more frequent in immunocompromised patients. The disseminated and pulmonary forms were the most common. Early clinical suspicion and appropriate samples and diagnostic assays, are crucial for early diagnosis and treatment.